Effect of Platelet Additive Solution (PAS) on Random Donor Platelet Concentrates - Saira Bashir , Iram Aftab, Sadia Akbar , Shabbir Hussian , Nusrat Bano , Shahida Mohsin (Journal of Rawalpindi Medical College, 2016)
Background: To observe in vitro parameters of stored platelets in PAS as compared to plasma for 10 days. Methods: A comparative study was carried out on 42 samples of random donor platelet concentrates (PC). They were divided into two groups of 21 samples each and stored in incubator at 22°C. In one group plasma was replaced with PAS. Sampling was done on day 0, 3, 5, 7, 8, 9 and 10. Bacterial cultures were carried out. All the samples,which showed contamination, were excluded from the study. Results: pH and glucose levels were reduced in both groups but they dropped more rapidly in PC stored in plasma than in PAS (p-value ≤ 0.001). However, the difference in LDH levels between two groups was not statistically significant. The mean values of PO2 were reduced whereas mean values of PCO2 were increased in both groups, but these changes were seen much less in PC stored in PAS (pvalue ≤ 0.001). The results showed that difference in all parameters between two groups was highly significant (p-value ≤ 0.001) except LDH. Conclusion: All the in vitro parameters were well preserved in PC stored in PAS than in plasma.